2006
DOI: 10.1037/0735-7044.120.6.1257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lesions of the bed nucleus of the stria terminalis, lateral hypothalamus, or insular cortex on conditioned taste aversion and conditioned odor aversion.

Abstract: The effects of permanent forebrain lesions on conditioned taste aversions (CTAs) and conditioned odor aversions (COAs) were examined in 3 experiments. In Experiment 1, lesions of the bed nucleus of the stria terminalis had no influence on CTA or COA acquisition. Although lesions of the lateral hypothalamus induced severe hypodipsia in Experiment 2, they did not prevent the acquisition of CTAs or COAs. Finally, in Experiment 3, lesions of the insular cortex retarded CTA acquisition but had no influence on COA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 89 publications
8
30
3
Order By: Relevance
“…The absence of increase in oscillatory activity in the granular zone contrary to the agranular zone in response to the first odor presentation confirms the functional heterogeneity of this cortex; however, a major finding is that IC (both aIC and gIC) presented a selective increase of beta oscillatory activity in response to the distal cue when the odor was ingested before intoxication. Although IC is strongly involved in gustatory food aversions (Bermú dez-Rattoni, 2004), its lesion or inactivation has been reported without effect on COA (Kiefer et al, 1982;Roman et al, 2006;Desgranges et al, 2009) and has led to ambiguous results on TPOA (Kiefer et al, 1982;Lasiter et al, 1985;Inui et al, 2006). Methodological differences used in these and our studies could account for the observed differences.…”
Section: An Effective Cs-us Association Duringcontrasting
confidence: 54%
“…The absence of increase in oscillatory activity in the granular zone contrary to the agranular zone in response to the first odor presentation confirms the functional heterogeneity of this cortex; however, a major finding is that IC (both aIC and gIC) presented a selective increase of beta oscillatory activity in response to the distal cue when the odor was ingested before intoxication. Although IC is strongly involved in gustatory food aversions (Bermú dez-Rattoni, 2004), its lesion or inactivation has been reported without effect on COA (Kiefer et al, 1982;Roman et al, 2006;Desgranges et al, 2009) and has led to ambiguous results on TPOA (Kiefer et al, 1982;Lasiter et al, 1985;Inui et al, 2006). Methodological differences used in these and our studies could account for the observed differences.…”
Section: An Effective Cs-us Association Duringcontrasting
confidence: 54%
“…Experiments from our laboratory show that neurotoxic lesions of the insular cortex disrupt the acquisition of conditioned taste aversions (CTAs), particularly when the taste stimulus is novel (Roman, Nebieridze, Sastre, & Reilly, 2006;Roman & Reilly, 2007). These results suggest that the insular cortex has a role in gustatory neophobia.…”
Section: Introductionmentioning
confidence: 75%
“…As indicated, CTA depends on a neural circuitry involving the insular cortex, also termed gustatory or taste cortex (Bermúdez-Rattoni 2004). Lesions or functional inactivation of the insular cortex block both the acquisition and retention of CTA (Nerad et al 1996;RamirezAmaya et al 1998;Cubero et al 1999;Roman et al 2006). The insular cortex is primarily involved in the association of the gustatory and visceral stimuli (Bermúdez-Rattoni 2004).…”
Section: Discussionmentioning
confidence: 99%